Source apportionment and ozone formation mechanism of VOCs considering photochemical loss in Guangzhou, China - FLORES RANGEL, ROSA MARIA (My University, 2023)
Understanding the sources and impact of volatile organic compounds (VOCs) on ozone formation is challenging when the traditional method does not account for their photochemical loss. In this study, online monitoring of 56 VOCs was carried out in summer and autumn during high ozone pollution episodes. The photochemical age method was used to evaluate the atmospheric chemical loss of VOCs and to analyze the effects on characteristics, sources, and ozone formation of VOC components. The initial concentrations during daytime were 5.12 ppbv and 4.49 ppbv higher than the observed concentrations in the summer and autumn, respectively. The positive matrix factorization (PMF) model identified 5 major emission sources. However, the omission of the chemical loss of VOCs led to underestimating the contributions of sources associated with highly reactive VOC components, such as those produced by biogenic emissions and solvent usage. Conversely it resulted in overestimating the contributions from VOC components with lower chemical activity such as liquefied petroleum gas (LPG) usage, vehicle emissions, and gasoline evaporation. Furthermore, the estimation of ozone formation may be underestimated when the atmospheric photochemical loss is not taken into account. The ozone formation potential (OFP) method and propylene-equivalent concentration method both underestimated ozone formation by 53.24 ppbv and 47.25 ppbc, respectively, in the summer, and by 40.34 ppbv and 26.37 ppbc, respectively, in the autumn. The determination of the ozone formation regime based on VOC chemical loss was more acceptable. In the summer, the ozone formation regime changed from the VOC-limited regime to the VOC-NOx transition regime, while in the autumn, the ozone formation regime changed from the strong VOC-limited regime to the weak VOC-limited regime. To obtain more thorough and precise conclusions, further monitoring and analysis studies will be conducted in the near future on a wider variety of VOC species such as oxygenated VOCs (OVOCs).
Keywords: Atmosfer Bilimleri ve Meteoroloji Mühendisliği; Mühendislik ve Teknoloji; Atmospheric Sciences and Meteorological Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yerbilimleri; METEOROLOJİ VE ATMOSFER BİLİMLERİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); GEOSCIENCES; METEOROLOGY & ATMOSPHERIC SCIENCES; Atmosfer Bilimi; Fizik Bilimleri; Atmospheric Science; Physical Sciences; Volatile organic compounds (VOCs); Photochemical age; Ozone pollution; Megacity